Parent-to-Child Violence: Does Gender Matter in Sentencing Decisions? - Chen, Gila (Crime & delinquency, 2022)
The purpose was to examine gender differences (a) in the sentencing severity for parent-to-child violence (PCV); and (b) in severity of PCV patterns. We analyzed 99 verdict cases in Israel. Two models, a logistic regression model and a generalized ordered logistic regression model, were applied. The findings of the first model indicated that being a woman reduced the odds of imprisonment by .106; furthermore, being tried after implementation of the 2012 reform in judicial discretion in sentencing significantly increased the odds of sentence severity by 2.85. The second model indicated that women had lower odds of being involved in severe violent offenses against their minor children compared with men (OR?=?0.31). The findings highlight the source of sentencing differentials.